1999
DOI: 10.1002/(sici)1096-911x(199911)33:5<441::aid-mpo1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of leukemia cells from children with common acute lymphoblastic leukemia for genomic sequences of the primate polyomaviruses JC virus, BK virus, and Simian virus 40

Abstract: Background An infectious etiology for childhood acute lymphoblastic leukemia (ALL) has long been suspected, although the characteristics of the putative childhood ALL‐inducing agent(s) remain a mystery. We describe the testing of ALL leukemia cells for the presence of DNA sequences of the polyomavirus family: JC virus, BK virus, and simian virus 40 (SV40). Procedure Cryopreserved leukemia cells from 25 children between 2 and 5 years of age at the time of diagnosis and classified as having “common” ALL (B‐precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…We, and others, have analyzed cALL samples for the presence of JC, and the related polyomavirus BK, with negative results. 22,23 Herpesviruses are alternative candidates. These viruses are widely distributed in nature, the timing of infection is related to living conditions, and several members of this virus family have known transforming properties, notably EBV and human herpesvirus-8 (HHV-8).…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have analyzed cALL samples for the presence of JC, and the related polyomavirus BK, with negative results. 22,23 Herpesviruses are alternative candidates. These viruses are widely distributed in nature, the timing of infection is related to living conditions, and several members of this virus family have known transforming properties, notably EBV and human herpesvirus-8 (HHV-8).…”
Section: Introductionmentioning
confidence: 99%
“…However, 17 of the hematologic malignancies were leukemias, while the most common type of neural tumor was neuroblastoma (seven cases). Laboratory studies have not identified SV40 in childhood leukemia or neuroblastoma specimens [8,34]. Conversely, considering childhood tumors with a proposed relationship to SV40, there was only one CPP child who developed ependymoma and this child's mother had not received poliovirus vaccine during pregnancy; there were no cases of choroid plexus tumor or osteosarcoma.…”
Section: Engels and Colleaguesmentioning
confidence: 99%
“…Only a limited number of published investigations have directly assayed pretreatment specimens for infectious agents at the time of cALL diagnosis and few have retrospectively analyzed archived prediagnostic specimens. More specifically, several small studies failed to detect the human polyomaviruses JC virus and BK virus in leukemia cells or stored newborn (Guthrie) blood spots (MacKenzie et al 1999; McNally and Eden 2004; Perzova et al 2000; Priftakis et al 2003; Smith et al 1999); one also failed to detect simian virus 40 (Smith et al 1999). Similarly, a few case–series and case–control studies failed to associate select human herpesviruses or human parvovirus B19 with the diagnosis of ALL (Bogdanovic et al 2004; Isa et al 2004; Luppi et al 1998; MacKenzie et al 2001; McNally and Eden 2004; O’Connor and Scadden 2000).…”
Section: Direct Evidence For Infectious Etiologymentioning
confidence: 99%